2001
DOI: 10.1111/j.1572-0241.2001.03874.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inadequate bowel preparation for colonoscopy

Abstract: Several patient characteristics were significantly associated with colonic preparation quality independent of preparation type, compliance with preparation instructions, and procedure starting time. This information may help to identify patients at an increased risk for inadequate colonic preparation for whom alternative preparation protocols would be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
237
6
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(272 citation statements)
references
References 15 publications
24
237
6
5
Order By: Relevance
“…Advanced age, comorbid illness and other factors contribute to a decreased ability of hospitalized patients to comply with oral preparation for colonoscopy [2,3] . In particular, a substantial number of patients are unable to consume the most commonly-prescribed regimen, large-volume PEG electrolyte solution, for colonoscopy preparation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced age, comorbid illness and other factors contribute to a decreased ability of hospitalized patients to comply with oral preparation for colonoscopy [2,3] . In particular, a substantial number of patients are unable to consume the most commonly-prescribed regimen, large-volume PEG electrolyte solution, for colonoscopy preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly among hospitalized patients, inadequate bowel preparation for colonoscopy may arise due to patient intolerance to the prescribed laxative regimen. In contrast to the ambulatory population, hospitalized patients are more often elderly and more likely to have co-existing conditions that impair their ability to ingest a large-volume laxative regimen [2,3] . Suboptimal bowel preparation may in turn lead to repeat endoscopic procedures, invasive interventions such as nasogastric tube insertion for administration of purgative agents, and additional days of hospitalization [4] hospital costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite more than 14 million colonoscopies being performed each year, the historic rates for adequate cleansing are unacceptably low and range from 70-82% (10)(11)(12)(13). Recent studies have shown that ingesting at least part of the purgative on the day of colonoscopy and coordinating the final dose of purgative with the start time of colonoscopy is more likely to result in adequate colon cleansing (2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study did not include inpatients who have been shown to have significantly worse bowel preps than outpatients presenting for colonoscopy. 21,22 These data combined with the current study in non-selected VHA patients clearly indicate that split dosing of PEG bowel preparations is effective and feasible.…”
Section: Discussionmentioning
confidence: 52%